(untitled) (Malaysian Management Journal, 2023)
The upstream oil and gas businesses in Nigeria suffer from insufficient absorptive capacity, poor knowledge management in their operations, and a lack of capability to address difficulties in the country effectively. These factors impeded their capacity to be strategically agile in reacting to the sector’s issues, eventually stifling their performance. This study investigated the moderating influence of knowledge management on the relationship between absorptive capacity and strategic agility in the upstream oil and gas industry of Nigeria. A survey research design was used. Instruments were sent to the upper and intermediate management of upstream oil and gas businesses in Lagos State. The validity and reliability of the instrument were examined, and the findings indicated that the questionnaire was valid and reliable. Smart Partial Least Square (PLS) 3.0 was used for data analysis, coupled with Structural Equation Modelling. The research indicated that absorptive capacity had a substantial impact on strategic agility and that knowledge management strengthened the association between absorptive capacity and strategic agility among the chosen upstream oil and gas enterprises in Lagos State, Nigeria. The study recommended that upstream oil and gas businesses employ good knowledge management methods and construct excellent absorptive capabilities to financially engage strategic agility measures that will guarantee greater success than their sector competitors. The study’s theoretical and managerial ramifications, as well as its limits and future research opportunities, were discussed.